Breast cancer in transgender female‐to‐male individuals: A case report of androgen receptor‐positive breast cancer. Issue 5 (20th November 2019) - Fundytus, Adam; Saad, Nathalie; Logie, Natalie; Roldan Urgoiti, Gloria
Abstract: Highlight the challenges associated with managing breast cancer in female‐to‐male (FtM) transgender individuals. This is a rare entity, requiring nuanced decision‐making regarding surgery as well as adjuvant therapies given the unique hormonal environment seen in individuals taking exogenous androgen as part of their gender identity. Contemporary case report derived from our clinical experience. Discussion focuses on a brief summation of all known cases of female‐to‐male breast cancer in FtM individuals described in the literature. A 48‐year‐old FtM transgender individual on exogenous testosterone for 19 years with stage IIA (pT1cN1M0), ER+(8/8), PR+(8/8), Androgen Receptor(AR)+(5%‐8%), Her‐2‐negative invasive ductal carcinoma of the breast. Due to AR positivity in tumor, cessation of testosterone was chosen after careful consideration of potential ramifications from both a cancer treatment as well as gender identity standpoint. Endocrinology consultation reassured the patient that identity affirming changes of facial hair growth and voice depth would persist after cessation of testosterone. Patient did not wish to undergo chemotherapy and as such was treated with combination of radiation to the axilla, adjuvant Anastrozole and testosterone cessation. Although breast cancer is rare in FtM transgender individuals, it can occur. Many FtM individuals take exogenous testosterone. It is important to test the tumor for the androgen receptor as this may have important implications for both gender identity and treatment. Additionally, the mastectomy commonly performed for "top" surgery in this population is not adequate for oncologic control by itself and at present there is no guidance regarding postsurgical screening in this population, especially in those individuals with a strong family history of breast cancer.